Sobre el teatre independent valencià i la nova escriptura teatral - Rosselló, Ramon X. (Caplletra. Revista Internacional de Filologia, 1997)
This article aims to study the independent Valencian drama (1968-1978) especially the activity of the groups who work with the Catalan language. In the first part there is a review of the development of this movement, centered above all on the relationship that these groups had with the Valencian drama tradition. The second part reviews the most remarkable dramatists and groups of the period: Josep Lluís Sirera, Rodolf Sirera, Manuel Molins and the Group 49, Pluja Teatre and Juli Leal and Carnestoltes.